2019
DOI: 10.3389/fphar.2019.01082
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated Morphine Affords a Prolonged Analgesia While Facilitating Extinction of Reward and Aversive Memories

Abstract: Morphine is thoroughly used for pain control; however, it has a high addictive potential. Opioid liposome formulations produce controlled drug release and have been thoroughly tested for pain treatment although their role in addiction is still unknown. This study investigated the effects of free morphine and morphine encapsulated in unilamellar and multilamellar liposomes on antinociception and on the expression and extinction of the positive and negative memories associated with environmental cues. The hot pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The pharmacokinetic studies were done using the previously reported protocols with minor changes [ 36 ]. Rats received one intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetic studies were done using the previously reported protocols with minor changes [ 36 ]. Rats received one intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons of the physicochemical properties and effects on drug activity between uni-and multi-lamellar liposomes have been reported. [15][16][17][18][19][20][21] Generally, liposomes are classified according to their preparation method. For example, liposomes prepared using a lipid thin-film hydration method tend to form multi-lamellar vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is highly addictive because the high concentration accesses the central nervous system, which normally occurs when the free form is administrated. Liposome formulations prolonged the analgesic effect and reduce addiction ( Gómez-Murcia et al, 2019 ). The formulation also significantly enhanced antitransit effects of morphine ( Pol et al, 1996 ).…”
Section: Construction Of Liposomal Systems For Medicinal Natural Prod...mentioning
confidence: 99%